Anesthesia and Oncology: Friend or Foe? - Buddeberg, Bigna S.; Seeberger, Manfred D. (Frontiers in Oncology, 2022)
Cancer is a leading cause of death, and surgery is an important treatment modality. Laboratory research and retrospective studies have raised the suspicion that the choice of anesthetics for cancer surgery might affect the course of cancerous disease. The aim of this review is to provide a critical overview of the current state of knowledge. Inhalational anesthesia with volatiles or total intravenous anesthesia (TIVA) with propofol are the two most commonly used anesthetic techniques. Most data comparing volatile anesthetics with TIVA is from either in vitro or retrospective studies. Although conflicting, data shows a trend towards favoring propofol. Opioids are commonly used in anesthesia. Data on potential effects of opioids on growth and recurrence of cancer are scarce and conflicting. Preclinical studies have shown that opioids stimulate cancer growth through the µ-opioid receptor. Opioids also act as immunosuppressants and, therefore, have the potential to facilitate metastatic spread. However, the finding of an adverse effect of opioids on tumor growth and cancer recurrence by some retrospective studies has not been confirmed by prospective studies. Regional anesthesia has not been found to have a beneficial effect on the outcome of surgically treated cancer patients, but prospective studies are scarce. Local anesthetics might have a beneficial effect, as observed in animal and in vitro studies. However, prospective clinical studies strongly question such an effect. Blood products, which may be needed during extensive cancer surgery suppress the immune system, and data strongly suggest a negative impact on cancer recurrence. The potential effects of other commonly used anesthetic agents on the outcome of cancer patients have not been sufficiently studied for drawing valid conclusions. In conclusion, laboratory data and most retrospective studies suggest a potential advantage of TIVA over inhalational anesthesia on the outcome of surgical cancer patients, but prospective, randomized studies are missing. Given the state of weak scientific evidence, TIVA may be used as the preferred type of anesthesia unless there is an individual contraindication against it. Studies on the effects of other drugs frequently used in anesthesia are limited in number and quality, and have found conflicting results.